2019
DOI: 10.3390/molecules24203672
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor Interacting Protein 1a (CRIP1a): Function and Structure

Abstract: Cannabinoid receptor interacting protein 1a (CRIP1a) is an important CB1 cannabinoid receptor-associated protein, first identified from a yeast two-hybrid screen to modulate CB1-mediated N-type Ca2+ currents. In this paper we review studies of CRIP1a function and structure based upon in vitro experiments and computational chemistry, which elucidate the specific mechanisms for the interaction of CRIP1a with CB1 receptors. N18TG2 neuronal cells overexpressing or silencing CRIP1a highlighted the ability of CRIP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…Cannabinoid receptor interacting protein 1a (but not 1b) contains a Class I PDZ ligand at its C-terminus (Niehaus et al, 2007) indicating a possible interaction with PDZ domaincontaining proteins. Furthermore, CRIP1a (but not 1b) contains a palmitoylation site that may facilitate partitioning to the membrane and thus association with CB1R (Niehaus et al, 2007;Booth et al, 2019).…”
Section: Cannabinoid Receptor Interacting Protein 1a and 1b (Crip1a/b)mentioning
confidence: 99%
“…Cannabinoid receptor interacting protein 1a (but not 1b) contains a Class I PDZ ligand at its C-terminus (Niehaus et al, 2007) indicating a possible interaction with PDZ domaincontaining proteins. Furthermore, CRIP1a (but not 1b) contains a palmitoylation site that may facilitate partitioning to the membrane and thus association with CB1R (Niehaus et al, 2007;Booth et al, 2019).…”
Section: Cannabinoid Receptor Interacting Protein 1a and 1b (Crip1a/b)mentioning
confidence: 99%
“…In the present study, we also observed that treatment with CRIP1a reversed the decrease in 14-3-3η expression induced by forebrain ischemia. CRIP1a has been reported to modulate cyclic adenosine 3 , 5 -monophosphate (cAMP) production, and expression of the 14-3-3η protein is regulated by cAMP and other cellular signals [40,47]. These results support that the expression level of 14-3-3η is closely associated with neuronal survival following forebrain ischemia and can be changed by the action of CRIP1a.…”
Section: Discussionmentioning
confidence: 64%
“…CRIP1a interacts with CB1R, suppressing the internalization of CB1R, which is essential for limiting glutamate release into the synaptic cleft [38]. The inhibition of internalization is caused by competing for β-arrestin [39,40], and it has been also reported that CRIP1a delivers newly synthesized CB1Rs to the presynaptic membrane without exogenous agonists of CB1R [41]. In hippocampal pyramidal neurons, CRIP1a overexpression prolongs the inhibition of excitatory currents induced by cannabinoids and decreases the severity of seizure [12], suggesting that treatment with CRIP1a may reduce ischemic neuronal damage by attenuating excitotoxicity in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the cannabinoid receptor interacting protein 1A (CRIP1A) is reported to influence CB 1 receptor agonist-induced regulation of excitatory neurotransmission, 99 to modulate which G i/o subtypes interact with CB 1 receptor, and to attenuate CB 1 receptor internalization via β-arrestin. 100 Splice variants and posttranslational modifications: Lastly, for both CB 1 and CB 2 receptors, splice variants have been reported in rodents and human. 44,[101][102][103] The in vivo significance of these variants has not yet been clarified, although differences in mRNA expression, receptor signaling, trafficking, and glycosylation have been reported.…”
Section: Neurobiology Of Cannabinoid Receptor Signaling -Lutzmentioning
confidence: 99%